Bullied Adolescent’s Life Satisfaction: Personal Competencies and School Climate as Protective Factors - Lázaro-Visa, Susana; Palomera, Raquel; Briones, Elena; Fernández-Fuertes, Andrés A.; Fernández-Rouco, Noelia (Frontiers in Psychology, 2019)
Although adolescence has been defined as a stage of vulnerability, due to the biopsychosocial changes that happen throughout this developmental stage, it is also one of growth. Some of the core personal competencies that have been identified to promote positive development at this stage while simultaneously preventing risks are: (1) a positive self-esteem, (2) self-regulation, (3) decision-making skills, (4) a moral belief system, and (5) prosocial connectedness. There are many factors and contexts that influence adolescent development. The school environment, for example, has the capacity to promote positive development and life satisfaction, yet on the other hand, it is a context within which different forms of violence, such as bullying, can occur. The principal aim of this study, therefore, is to analyze the influence that bullying has on one’s life satisfaction, while taking into account participants’ socio-demographic characteristics (i.e. gender and developmental stage), their core personal competencies (i.e. self-esteem, empathy, problem resolution strategies, repair of negative emotions and values), and the school climate. To obtain data, a hierarchical regression analysis was conducted with a sample of 647 Spanish students (53.3% female), ranging in age from pre- (10-13 years old; 60.3%) to mid-adolescence (14-18 years old; 39.7%) and belonging to diverse socio-economic contexts (15.3% rural) and schools (32.1% public). After gaining informed consent from both the participants and their parents, students completed the survey voluntarily and under anonymity. Results show gender, developmental stage, and having been bullied as predictors of participants’ levels of life satisfaction. Among the personal competencies assessed, self-esteem, emotional repair skills, and social values were those which demonstrated the most significant effect on one’s life satisfaction. Finally, after taking school climate into account, gender, developmental stage, experience with bullying and social values did not prove to be significant predictors towards one’s life satisfaction, though self-esteem, and emotional repair did. These results have important implications for education objectives, methodologies, and school functioning, which have the capacity to promote adolescent life satisfaction and to prevent the consequences of bullying, while at the same time attend to self-esteem, emotional repair competencies, and particularly, to school climate.